Correction: How the magnetic field impacts the chiroptical activities of helical copper enantiomers. (26th October 2021) - Wu, Jialu; Li, Bo; Wang, Hong; Lai, Yingzhen; Ye, Yue; Zou, Yongkang; Tian, Jumei; Xu, Yaohua
Abstract : Correction for 'How the magnetic field impacts the chiroptical activities of helical copper enantiomers' by Jialu Wu et al., New J. Chem., 2021, DOI: ; 10.1039/D1NJ03803F .